2017
DOI: 10.1038/cr.2017.99
|View full text |Cite
|
Sign up to set email alerts
|

Ythdc2 is an N6-methyladenosine binding protein that regulates mammalian spermatogenesis

Abstract: N-methyladenosine (mA) is the most common internal modification in eukaryotic mRNA. It is dynamically installed and removed, and acts as a new layer of mRNA metabolism, regulating biological processes including stem cell pluripotency, cell differentiation, and energy homeostasis. mA is recognized by selective binding proteins; YTHDF1 and YTHDF3 work in concert to affect the translation of mA-containing mRNAs, YTHDF2 expedites mRNA decay, and YTHDC1 affects the nuclear processing of its targets. The biological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
723
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 799 publications
(779 citation statements)
references
References 53 publications
22
723
1
5
Order By: Relevance
“…4c). These results could be due to other reader proteins such as YTHDF1, YTHDF3 and YTHDC2, which redundantly mediate m 6 A/m-dependent mRNA stability 21,22,26 . These reader proteins might compensate its function following YTHDF2 knockdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). These results could be due to other reader proteins such as YTHDF1, YTHDF3 and YTHDC2, which redundantly mediate m 6 A/m-dependent mRNA stability 21,22,26 . These reader proteins might compensate its function following YTHDF2 knockdown.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, YTHDF3, cooperates with either YTHDF1 or YTHDF2 to promote translation or degradation of transcripts, respectively 23,24 . YTHDC1 has been implicated in splicing whereas YTHDC2 is implicated in both translation and degradation 25,26 .…”
mentioning
confidence: 99%
“…The effect of m 6 A modification on mRNA transcripts is mediated by specific m 6 A binding proteins, which are also known as m 6 A readers (24). The YTH domain family proteins YTHDF1-3 and YTH domain containing 1-2 have been identified as m 6 A-binding proteins in mammals (35,36,46,59). YTHDF2 recognizes and destabilizes m 6 A-containing mRNA (35), whereas YTHDF1 and YTHDF3 regulate mRNA translation and promote protein synthesis (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…showed that YTH domain family protein 3 (YTHDF3) promoted translation in synergy with YTHDF1 and affected methylated mRNA decay mediated through YTHDF2 30. And recently, researchers have found that YTHDC2 promotes translation efficiency and decreases the mRNA abundance 31. Apart from the YTH domain family, certain proteins in the heterogeneous nuclear ribonucleoprotein family also act as “readers”.…”
Section: The Discovery Of M6a and Its Functionmentioning
confidence: 99%